What makes up a central exit examination? - Florian Birkenfeld (Friedrich-Alexander-Universität Erlangen-Nürnberg, Bavarian Graduate Program in Economics (BGPE), 2008)
A large number of econometric studies have examined the impact of central exit examinations on student attainment and repeatedly found a positive effect. This paper contributes to clarify the term central exit examination by distinguishing between central assignment and central grading. For this purpose, I use a study from Birkenfeld und Hanafy (2008), who have gathered the relevant information for the 16 German federal states. First econonometric analyses show, that the distinction between central assignment and central grading is indeed fruitful.
Keywords: I21; I28; 330; central exit examination; school systems